Pengaruh Karakteristik Gaya Penyusunan Anggaran terhadap Efisiensi Biaya - Johan Arifin (Universitas Islam Indonesia, 2007)
The main aim of this research was to find out how far the influence of the characteristics of budget preparation style was on the cost efficiency of manufacture companies in Jakarta Stock Exchange in the period of 2004. According to a survey of 32 manufacture companies the result of the analysis showed that all variables of the budget preparation characteristics style had significant influences on cost efficiency variables. In partial analysis, however, only two of the five variables i.e. the distinctiveness of the budget goals and budget evaluation had significant influences on the cost efficiency variables.Keywords: budget preparation style, cost efficiency